Contribución al conocimiento de la biología y taxonomía de un hongo del género phytium aislado del "aliso", alnus acuminata hbk (1990)
Some biological aspects of an isolated fungus of Alnus acuminata roots were studied. It bas been found Tbat between OOC and 4°C tbe fungi grows fast. This condition can result in a important factor in the ecophysiology of 'Aliso' populations, that grows in secondary forests at sub-paramo, After a review of the taxonomic literature, we placed it in the Phytium genus, but not in a particular described species. We assume that it is a new species. We modificated the microculture technique that was simpler and safer and them we made direct observations about tbe fungus growtb and development. As for now it is nominated as Phytiun near Mammillatum Meurs. Palabras Claves: Phytium, bongos, A/nus acuminata HBK., "Aliso".